Tworzenie zespołów w warunkach postępujących zmian w organizacji - Kopertyńska, Maria Wanda (Formation of teams in face of progressive changes in an organization, 2006)
Changes in internal and externa] environment are forcing many changes in companies. These changes require constant modifications as well as seeking new areas of improvements throughout all departments of a company. As a result, in recent years there has been a drastic decline in the number of organizations relying solely on individuals carrying out specific tasks, and an increase of importance of team's based work. The article shows ideas related to creating and functioning of teams in practice.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 624-630